High aspect ratio microdisplay and thin optical component for glass-like AR devices. Issue 3 (3rd July 2021) - Kang, Chan-mo; Shin, Jin-Wook; Choi, Sukyung; Kwon, Byoung-Hwa; Cho, Hyunsu; Cho, Nam Sung; Lee, Jeong-Ik; Lee, Hyunkoo; Lee, Jeong Hwan; Kim, Hokwon; Cho, Ara; Park, Sang Hyun; et al.
Abstract : Organic light-emitting diode (OLED) microdisplays have attracted much attention as displays for small form factor augmented reality (AR) devices. To realize glass-like thin and wide field of view (FoV) AR devices, we designed a display module with a high aspect ratio microdisplay and a thin optical component. For the high aspect ratio microdisplay, we developed the color OLED microdisplay with a 32:9 aspect ratio and a 0.8-inch diagonal ∼2, 490-ppi CMOS backplane. To express color and reduce optical crosstalk, we fabricated the color filter (C/F) patterning directly on the white OLED. We also developed a pin mirror lens with 11 pin mirrors to improve the optical efficiency and quality with a thin lens. By combining the microdisplay with LetinAR's pin mirror lens, we successfully demonstrated an AR device with a wide horizontal FoV of 46° but with a small form factor 4 mm lens.